Spontaneous hepatic haemorrhage secondary to ruptured hepatocellular adenoma in a young male patient. Issue 8 (25th August 2020) - Yoon, Peter Daechul; Chen, Andy Ze Lin; Tovmassian, David; Pleass, Henry
Abstract : A 27-year-old man presented with acute right upper quadrant abdominal pain and vomiting. He was clinically in hypovolaemic shock. Investigations revealed normocytic anaemia with a normal bilirubin and moderate liver function test abnormalities. CT abdomen and pelvis demonstrated haemoperitoneum and a large solitary hepatic mass in segments V and VI, suspicious for a ruptured hepatic tumour. Massive transfusion protocol was commenced and angioembolisation of the inferior branch of the right hepatic artery was undertaken. Despite this, his haemorrhagic shock was resistant to resuscitation. Thus, he underwent emergent exploratory laparotomy, which resulted in segments V and VI liver resection and packing. Re-look laparotomy 2 days following initial exploration was performed where haemostasis was confirmed. Histopathology revealed a ruptured well-differentiated hepatocellular adenoma. The patient made a good recovery following a 2-week admission.